Analisis Hermeneutika Schleiermacher Terhadap Puisi "Tak Harus Sedarah untuk Menjadi Saudara" Karya Eko Saputra Poceratu: Penelitian - Felani Soplanit (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to analyze the meaning of the poem “Tak Harus Sedarah untuk Menjadi Saudara” by Eko Saputra Poceratu using Friedrich Schleiermacher’s hermeneutic approach. This study employs an interpretive qualitative approach with a descriptive design. Data were obtained from the poem text as primary data, as well as from in-depth interviews with the poet, and were supported by various literature on hermeneutics and literary criticism. The analysis was conducted through grammatical interpretation of linguistic elements, such as diction, style, sentence structure, and textual meaning, as well as psychological interpretation to understand the author’s thought process, experiences, and intentions. The results of the study indicate that this poem constructs the meaning of universal brotherhood through simple diction, metaphors, repetition, and rhetorical questions that reinforce its criticism of discrimination based on religion, ethnicity, regional origin, and social status. Psychologically, the poem reflects the poet’s concern for the realities of social injustice, intolerance, and development disparities, particularly those experienced by communities in Eastern Indonesia. The integration of these two forms of interpretation leads to the understanding that true brotherhood is built on the foundations of love, justice, respect for human dignity, and solidarity in diversity. This study enriches the application of Schleiermacher’s hermeneutics in the study of contemporary Indonesian literature while affirming the relevance of humanistic values to the lives of Indonesia’s diverse society.